2021
DOI: 10.1002/jsfa.11247
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of (–)‐epigallocatechin‐3‐gallate and protein isolate from large yellow croaker (Pseudosciaena crocea) roe: improvement of antioxidant activity and structural characteristics

Abstract: BACKGROUND: Large yellow croaker (Pseudosciaena crocea) roe is the main by-product in the processing of large yellow croaker. Previous studies have found that its protein isolates are composed of vitellogenin, as well as vitellogenin B and C, having good functional properties. (-)-Epigallocatechin-3-gallate (EGCG) is a natural antioxidant component that can be combined with protein to improve antioxidant activity and structural characteristics of protein.RESULTS: EGCG was bound with the P. crocea roe protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The secondary structures of krill protein were determined according to a previously reported method 20 . The spectra were recorded by utilizing an infrared spectrophotometer (Perkin Elmer, Salem, MA, USA) from 4000 to 400 cm −1 at a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary structures of krill protein were determined according to a previously reported method 20 . The spectra were recorded by utilizing an infrared spectrophotometer (Perkin Elmer, Salem, MA, USA) from 4000 to 400 cm −1 at a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The secondary structures of krill protein were determined according to a previously reported method. 20 The spectra were recorded by utilizing an infrared spectrophotometer (Perkin Elmer, Salem, MA, USA) from 4000 to 400 cm −1 at a resolution of 4 cm −1 . OMNIC Spectra v. 8.2 (Thermo Fisher Scientific, Waltham, MA, USA) was used to fit the amide I band (1700-1600 cm −1 ) and to calculate the relative amount of the secondary structure of krill protein.…”
Section: Fourier Transform Infrared Spectroscopy Measurementsmentioning
confidence: 99%
“…Du et al demonstrated that the EGCG–large yellow croaker ( Pseudosciaena crocea ) roe protein isolate (pcRPI) conjugate prepared by free-radical method exhibited higher weight-average molar mass, thermal stability, and antioxidant activity than the native pcRPI. However, the exact site of interaction between EGCG and pcRPI remained unclear …”
Section: Mechanisms Underlying the Modification Of Aquatic Protein Vi...mentioning
confidence: 99%
“…Among them, the antioxidant capacity of polyphenol–protein conjugates was closely related to the preparation approach and the type of phenolic compounds used. For example, the radical scavenging and reducing power of large yellow croaker roe protein isolates were remarkably increased by 2.5- and 1.4-fold, respectively, after grafting with EGCG . The conjugates of EGCG and scallop gonad protein showed 4.9 times and 7.4 times higher 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging and oxygen radical absorbance capacity (ORAC) than that of native scallop protein, and the covalent complexes of EGCG and scallop proteins had higher antioxidant activity than noncovalent mixtures .…”
Section: Mechanisms Underlying the Modification Of Aquatic Protein Vi...mentioning
confidence: 99%
“…With the rapid development of new drugs and treatment technologies, the use of natural substances, especially Chinese herbal medicines (unit herbal medicines, compound formulations, etc.) in the treatment of antioxidant-related diseases has attracted much attention (Du et al, 2021;Hassan et al, 2014Hassan et al, , 2017Hassan & Al-Rawi, 2013;Zou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%